Bemo Rejuvenation and Social Conflict in Jakarta 1995-1997 - Aqila Zahra; Eka Yudha Wibowo (JUSPI (Jurnal Sejarah Peradaban Islam), 2026)
This article examines the renewal policy of bemo in DKI Jakarta during 1995-1997 and its social impacts on bemo drivers and owners. It addresses two questions: how the policy was implemented and what economic, administrative, operational and social problems emerged during the transition from bemo to Angkutan Pengganti Bemo (APB). This study employs the historical method, consisting of heuristics, source criticsm, interpretation and historiography. Primary sources consist of newspaper archives between 1995 and 1997 and photographic archives from the National Library of Indonesia, supplemented by books, theses and scholarly articles. The findings show that the policy was implemented through the replacement of registered bemo with four wheeled venichles and the regulation APB routes. Its impelentations, however, faced low compensation for old vehicles, cotsly down payments and installments, incomplate vehicle documents, delayed route permits, organizational levies and route conflicts. Consequently, the policy only partially replaced the old fleet and placed small scale drivers and owners in a more vulnerable economic position. The study concludes that transport modernization was not merely a technical policy but also reshaped the livelihoods of informal transport actors.